2020
DOI: 10.3390/jcm9051244
|View full text |Cite
|
Sign up to set email alerts
|

Speckle Tracking-Derived Left Atrial Stiffness Predicts Clinical Outcome in Heart Failure Patients with Reduced to Mid-Range Ejection Fraction

Abstract: Background and Aim: Left atrial stiffness (LASt) is an important marker of cardiac function, especially in patients with heart failure (HF); it explains symptoms on the basis of pressure transfer to the pulmonary circulation. The aim of this study was to evaluate the relationship between LASt and cardiac events (CE) in HF patients with reduced to mid-range ejection fraction. Methods: The study included 215 consecutive ambulatory HF patients with ejection fraction (EF) < 50% (162 HF reduced EF and 53 HF mid-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 36 publications
1
13
0
2
Order By: Relevance
“…In a recent study, Reddy et al found that LA Stiff may be the best echocardiographic correlate of elevated filling pressures in patients with preserved LVEF 19 . Finally, abnormal LA Stiff values were associated with an increased incidence of cardiac events 8 and were a strong predictor of atrial fibrillation recurrence 20 . Combining E/Ea and LAS, LA Stiff is strongly influenced by LV properties 21 and is mainly modulated by LV longitudinal function through the downward motion of the mitral plane during ventricular systole.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In a recent study, Reddy et al found that LA Stiff may be the best echocardiographic correlate of elevated filling pressures in patients with preserved LVEF 19 . Finally, abnormal LA Stiff values were associated with an increased incidence of cardiac events 8 and were a strong predictor of atrial fibrillation recurrence 20 . Combining E/Ea and LAS, LA Stiff is strongly influenced by LV properties 21 and is mainly modulated by LV longitudinal function through the downward motion of the mitral plane during ventricular systole.…”
Section: Discussionmentioning
confidence: 96%
“…LA Stiff showed a more robust correlation with the extent of LA fibrosis than LA strain 7 . The prognostic utility and clinical relevance of LA Stiff have been recently emphasized 8,9 . However, LA Stiff has not yet been investigated in patients with c‐LVOO correction, a specific population at risk of premature LV and LA dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…LAS_r has also been used in calculating a surrogate of LA stiffness (calculated as the ratio of E/e’ to LAS_r) [ 52 , 87 , 88 ]. LA stiffness was a strong predictor of adverse outcomes (death and HF hospitalization) in a study of 215 HF patients [ 87 ].…”
Section: Prognostic Value Of La Deformationmentioning
confidence: 99%
“…Such changes, in the absence of mitral valve disease, reflect significant diastolic LV disease and raised diastolic pressures. (Bytyçi et al., 2020 Apr 25; Khurraml et al., 2016; Melenovsky et al., 2015) Being chronic in nature and perpetual in deterioration, the LA response to increased cavity pressure is in the form of enlargement, remodelling and finally fibrosis. (Bytyçi et al., 2019) These changes result in worsening cavity function including contraction and stiffness, which eventually result in raised cavity pressure and pulmonary venous hypertension.…”
Section: Discussionmentioning
confidence: 99%